Enkele gedagtes oor "n kerkorde - Coertzen, Pieter (Hervormde teologiese studies, 1992)
Reflections on a church order In this article a church order as a book of rules and regulations of a church is discussed. A church order does not represent a neutral position. On the contrary, it is based on important theological principles. Some of these principles are discussed with regard to the following themes: What is a church order?; Scripture, confession of faith and a church order; The function of a church order; Rules for the handling and interpretation of a church order.